In vitro culture techniques for forage genetic resources - Hanson, Jean; Ruredzo, T.J. (International Crops Research Institute for the Semi-Arid Tropics, 1992)
Briefly outlines results of a research carried out at ILCA since 1986 on in vitro culture technology of Cynodon aethiopicus, C. dactylon, Digitaria decumbens, Sesbania sesban, Leucaena leucocephala, Erythrina brucei, Faidherbia albida and Acacia tortilis.